EFFECT OF DUST METALS AND COMPOST ON GROWTH OF Gundelia tournefortii L. AND CHEMICAL COMPOSTION OF IT᾿S EDIBLE PORTION - Vian Dler Ali; Farhad Hassan Aziz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was conducted at the Grdarasha Research Field station, College of Agricultural Engineering Sciences, Salahaddin University – Erbil using randomized complete block design (RCBD) during the years 2019-2021 to study the effect of five levels 0, 5, 10, 15 and 20 g of dust metals of Erbil steel factory (size 2mm mesh) in combination with compost of solid waste management and sorting of Akre district-Duhok province on growth, yield and chemical composition of Gundelia tournefortii L. The results indicated that powdery metal dust and compost fertilizer significantly increased length, diameter, fresh weight and dry weight of edible portion, and thus escalated the total yield of this plant for the two growing seasons. The highest value (669.07g/m2) of total yield was recorded by application 20g of dust metals combined with compost fertilizer in the second year. Chemical composition of edible portion also affected by fertilizer application Fe%, Co, Ni, Cu, Zn, Se, Hg and Pb ppm. The results reviewed that the addition of mineral dust as nutrients and compost fertilizer significantly enhanced the concentration of these above elements in edible portion. The maximum response was obtained with the high levels of mineral treatments for all studied elements as compared with control.